Reversible uptake of CO2 by pincer ligand supported dimetallynes - Caise, A; Griffin, LP; McManus, C; Heilmann, A; Aldridge, S (Wiley, 2022)
We report on the reversible uptake of carbon dioxide by dimetallynes featuring ancillary hemi-labile pincer ligands. Insertion into the Ge-Ge/Sn-Sn bonds yields species containing an E(CO 2 )E unit, with the mode of ligation of the CO 2 fragment determined crystallographically being found to be dependent on the identity of the group 14 element. The thermodynamics of CO 2 uptake/loss can be established through VT-NMR (ΔH° = +24.6(2.3) kJ mol -1 , ΔS° = +64.9(3.8) J mol -1 K -1 , ΔG° 298 = +5.3(1.9) kJ mol -1 for the loss of CO 2 in the Ge case), and the chemical consequences of reversibility demonstrated by thermodynamically-controlled exchange reactions.